2020
DOI: 10.1590/1413-81232020254.19222018
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards body weight dissatisfaction associated with adolescents’ perceived health and sleep (PeNSE 2015)

Abstract: This study aimed to investigate whether attitudes towards body weight dissatisfaction is associated with perceived health and impairments in sleep among a national population-based sample of Brazilian adolescents. This is a cross-sectional data from the 2015 National School-Based Health Survey (PeNSE). A total of 100.182 students (70.8% were between 14 to 15) in ninth-grade, enrolled in public and private schools were eligible for data analysis. Variables were measured using a questionnaire and binary logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
4
2
1
Order By: Relevance
“…The majority of participants getting sufficient sleep seven hours or more, but it was observed that no significant association with body image. The result was not in line with our findings; previous studies found that bodyweight dissatisfaction has been associated with sleep impairment [60].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The majority of participants getting sufficient sleep seven hours or more, but it was observed that no significant association with body image. The result was not in line with our findings; previous studies found that bodyweight dissatisfaction has been associated with sleep impairment [60].…”
Section: Discussioncontrasting
confidence: 99%
“…However, no significant association of meals with body image recognized. Our finding did not support previous study that suggested meal patterns and food consumption were associated with body dissatisfaction and overfat status among adolescents [60]. Some previous studies reflect that the number of meals taken a day was inversely related to obesity [61][62][63].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, body image was the strongest significant predictor of HRQoL in children and adolescents (8). Previous findings have frequently demonstrated the relationship between body dissatisfaction with sleep impairment, sadness/loneliness, peer stress, depression, and low self-esteem (9,(37)(38)(39). The aforementioned problems would contribute to the impairment of adolescents' emotional and social functioning and explain how negative body image may result in poorer HRQoL in adolescents.…”
Section: Discussionmentioning
confidence: 85%
“…It is also documented that negative body image is associated with obesity-related lifestyle factors, including low levels of physical activity, unhealthy eating habits, and disordered eating (6,7). Previous studies documented the significant relationship between body image and healthrelated quality of life (HRQoL) (8,9). According to the existing evidence, lifestyle components, including physical activity and eating habits, have been significantly associated with obesity and HRQoL (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…For purposes of analysis, answer categories were pooled as follows to yield a dichotomous positive/negative classification: very important/important and not very important/not important; very satisfied/satisfied and indifferent/dissatisfied/very dissatisfied, respectively. 14 …”
Section: Methodsmentioning
confidence: 99%